INM004: Polyclonal Neutralizing Antibodies Against Shiga Toxin as a Treatment for Hemolytic Uremic Syndrome - Marta Rivas; Mariana Pichel; Vanesa Zylberman; Mariana Colonna; Marina Valerio; Carolina Massa; Romina Pardo; Andrés E. Ciocchini; Santiago Sanguineti; Ian Roubicek; Linus Spatz; Fernando Alberto Goldbaum (Toxins)
Hemolytic uremic syndrome (HUS) is a thrombotic microangiopathy characterized by microangiopathic hemolytic anemia, thrombocytopenia, and acute kidney injury (AKI). Shiga toxin (Stx)-producing Escherichia coli-associated HUS (STEC-HUS) is one of the leading causes of AKI in children. Approximately 1.5 to 3% of children die during the acute phase, and about 30% experience long-term renal sequelae. Argentina has the highest incidence of STEC-HUS globally. Given the prominent role of Stx in its pathophysiology, STEC-HUS is considered more of a toxemia than a bacterial disease. Stx transport occurs before and after the STEC-HUS onset, allowing for the distinction between an early toxemia phase and an advanced toxemia phase. In this review, we present our efforts to develop INM004, an anti-Stx treatment aimed at ameliorating or preventing the clinical consequences of STEC-HUS. We describe the protein engineering that facilitated this development and the clinical path to demonstrate the safety and efficacy of INM004. This immunotherapy could represent a new step in the treatment of STEC-HUS, which could potentially prevent long-term damage. If phase 3 trials are successful, earlier and broader use of INM004 is envisioned. We also discuss the potential impact of INM004 therapy, targeted vaccination strategies, and new diagnostic tools for this disease.